Promising results of associating liver partition and portal vein ligation for staged hepatectomy for perihilar cholangiocarcinoma in a systematic review and single-arm meta-analysis - Golriz, Mohammad; Ramouz, Ali; Hammad, Ahmed; Aminizadeh, Ehsan; Sabetkish, Nastaran; Khajeh, Elias; Ghamarnejad, Omid; Carvalho, Carlos; Rio-Tinto, Hugo; Chang, De-Hua; Joao, Ana Alagoa; Goncalves, Gil; et al. (Cancers, 2024)
Background: ALPPS popularity is increasing among surgeons worldwide and its indications are expanding to cure patients with primarily unresectable liver tumors. Few reports recommended limitations or even contraindications of ALPPS in perihilar cholangiocarcinoma (phCC). Here, we discuss the results of ALPPS in patients with phCC in a systematic review as well as a pooled data analysis. Methods: MEDLINE and Web of Science databases were systematically searched for relevant literature up to December 2023. All studies reporting ALPPS in the management of phCC were included. A single-arm meta-analysis of proportions was carried out to estimate the overall rate of outcomes. Results: After obtaining 207 articles from the primary search, data of 18 studies containing 112 phCC patients were included in our systematic review. Rates of major morbidity and mortality were calculated to be 43% and 22%, respectively. The meta-analysis revealed a PHLF rate of 23%. One-year disease-free survival was 65% and one-year overall survival was 69%. Conclusions: ALPPS provides a good chance of cure for patients with phCC in comparison to alternative treatment options, but at the expense of debatable morbidity and mortality. With refinement of the surgical technique and better perioperative patient management, the results of ALPPS in patients with phCC were improved.
Gesehen am 09.10.2024